A 2.5 min cold water immersion improves prolonged intermittent sprint performance - Egaña, M.; Jordan, L.; Moriarty, T. (Journal of Science and Medicine in Sport, 2019)
Objectives: We investigated if cold water immersion (CWI) affects exercise performance during a prolonged intermittent sprint test (IST), designed to mimic activity patterns of team-sports. Design: Randomized-crossover design. Methods: Ten male team-sport players completed 3 IST protocols (two 40-min "halves" of repeated 2-min blocks consisting of a 8-s "all-out" sprint, 100-s active recovery and 12-s rest) on a cycle ergometer at normothermic conditions. Each "half" was separated by a 15 min recovery period of either: (i) passive rest, (ii) 5-min CWI at 8 °C (CWI-5) or (iii) 2.5-min CWI at 8 °C (CWI-2.5), in a random counterbalanced order. Results: Physical performance, core temperature (Tcore) and heart rate were not different among conditions in the first half. In the passive rest trial, total work (TW) and peak power (PP) were lower during the second half (TW: 5.04 ± 1.11 kJ; PP: 929 ± 286 W) than the first half (TW: 5.66 ± 1.02 kJ; PP: 1009 ± 266 W); while TW and PP were not different between halves following CWI-5 (first half, TW: 5.34 ± 1.02 kJ, PP: 1016 ± 283 W; second half, TW: 5.19 ± 1.38 kJ; PP: 996 ± 318 W) and CWI-2.5 (first half, TW: 5.47 ± 1.19 kJ, PP: 966 ± 261 W; second half, TW: 5.25 ± 1.17 kJ; PP: 952 ± 231 W). Tcore was lower until the 20th minute of the second half after CWI-5 and CWI-2.5 compared with passive rest. Conclusions: A post-exercise 2.5-5-min CWI attenuates the reductions in prolonged sprint performance that occur in the second half of team sports, due, at least partly, to reductions in core temperature and associated increase in heat storage.